Rare Cause of Leg Edema after Femoropopliteal Bypass Procedure in Patient with Previously Unrecognized Arteriovenous Fistulas: A Case Report - Babic, Srdjan; Babic, Aleksandar; Marinkovic, Milan; Kovacevic, Vladimir; Vucurevic, Bojan; Tanaskovic, Slobodan; Sevkovic, Milorad; Gajin, Predrag; Matic, Predrag; Ilijevski, Nenad (Open Access Macedonian Journal of Medical Sciences, 2023)
BACKGROUND: Arteriovenous fistulas (AVFs) are pathological, congenital, or acquired communications between the arterial and venous vascular bed. Asymptomatic AVFs do not require surgical or endovascular treatment; however, if they are symptomatic, they must be treated to relieve the patient of symptoms and cardiovascular disorders. CASE PRESENTATION: Our patient had an undiagnosed AVF that became symptomatic after femoropopliteal bypass surgery. We successfully treated these complications with four cover stents. CONCLUSION: The presence of AVFs should be kept in mind in the case of rapidly developing leg edema after revascularization. Endovascular treatment of symptomatic AVF is a safe and effective treatment modality. Treatment of symptomatic AVFs is not only recommended for improving impaired arterial or venous blood flow, but also for preventing recurrent PE.